Investigate the application of postoperative ctDNA-based molecular residual disease detection in monitoring tumor recurrence in patients with non-small cell lung cancer——A retrospective study of ctDNA - Zhang, Xuefei; Zhang, Youguo; Zhang, Shanli; Wang, Sha; Yang, Peng; Liu, Changhong (Frontiers in Oncology, 2023)
Purpose: To evaluate whether postoperative circulating tumor DNA (ctDNA) in plasma of patients with non-small cell lung cancer (NSCLC) can be used as a biomarker for early detection of molecular residual disease (MRD) and prediction of postoperative recurrence. Methods: This study included 73 patients who underwent radical surgery operation followed by adjuvant therapy for NSCLC，58.9% at stage IA. Tumor tissue and blood samples before and after operation were collected. ctDNA analysis were performed using next generation sequecing (NGS). Molecular residue disease (MRD) positive was defined as ctDNA positive 1-3 days after surgery operation. Results: Positive post-operatively ctDNA was associated with shorter recurrence-free survival (RFS). (HR7.8, 95%CI 0.0-30.3; P=0.000）The status of MRD was a strong predictor of disease recurrence (HR 7.8, 95% CI 0.0-30.26; P=0.000). MRD-positive patients who received adjuvant therapy had improved RFS compared to those who did not (mean RFS: 18.5 months vs. 12.3 months; HR7.8, 95% CI0.0-30.26; P<0.05). The RFS of MRD-negative patients receiving adjuvant therapy was even shorter than that of patients not receiving adjuvant therapy (mean RFS 32.2 months versus 64.8 months; P<0.05). After adjustment for clinicopathological variables, adjuvant therapy remained an independent factor affecting RFS in MRD-positive patients (P=0.002), but not in MRD-negative patients (P = 0.283). Conclusions: Post-operative ctDNA analysis is an effective method for recurrence risk stratification of NSCLC, which is beneficial to the management of patients with NSCLC.